Polycyclic aromatic hydrocarbons in wild and farmed whitemouth croaker and meagre from different Atlantic Ocean fishing areas: Concentrations and human health risk assessment - Oliveira, Marta; De Gasperi Portella, Carolina [UNESP]; Ramalhosa, Maria João; Delerue-Matos, Cristina; Sant'Ana, L. S. [UNESP]; Morais, Simone (Elsevier, 2020)
This work assessed the concentrations of 18 polycyclic aromatic hydrocarbons (PAHs) in edible tissues of whitemouth croaker (Micropogonias furnieri) and meagre (Argyrosomus regius) captured in different Atlantic Ocean fishing areas and available to Brazilian and Portuguese consumers. Total PAH (∑PAHs) levels ranged from 1.32 to 5.41 μg/kg ww in wild-caught croaker and 2.66 (wild)-18.0 (farmed) μg/kg ww in meagre. Compounds with 2- and 3-rings represented 54–86% of ∑PAHs in the muscle tissues of wild-caught species (croaker and meagre) being naphthalene, fluorene, and phenanthrene the predominant compounds. ∑PAHs in farmed meagre were 4–7 times higher than in wild-caught meagre, with 2-, 3-, 4-, 5-, and 6-ring compounds representing 15, 18, 44, 22, and 1% of ∑PAHs, respectively. Benzo(a)pyrene levels in farmed meagre varied between 0.06 and 0.34 μg/kg ww. Crude oil refining and combustion sources were identified as the major sources of PAHs in FAO 27, 34 and 41 Atlantic Ocean fishing areas. The biometric characteristics (length, weight, moisture, and fat content) and ∑PAHs allowed to discriminate between wild-caught and farmed meagre samples and between meagre and croaker. Assessment of carcinogenic risks suggested that a diet exclusive on farmed meagre may pose additional risks for the health of European top consumers fish.
Keywords: Croaker; Daily exposure; Fish consumption; Meagre; Polycyclic aromatic hydrocarbons (PAHs); Risk assessment